2022
DOI: 10.3390/children9101568
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Non-Pharmacological Methods, Such as Breastfeeding, to Mitigate Pain in NICU Infants

Abstract: Neonates do experience pain and its management is necessary in order to prevent long-term, as well as, short-term effects. The most common source of pain in the neonatal intensive care unit (NICU) is caused by medically invasive procedures. NICU patients have to endure trauma, medical adhesive related skin injuries, heel lance, venipuncture and intramuscular injection as well as nasogastric catheterization besides surgery. A cornerstone in pain assessment is the use of scales such as COMFORT, PIPP-R, NIPS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 120 publications
1
6
0
1
Order By: Relevance
“…Parents' experiences with IPC in the context of neonatal pain management has not previously been studied, so our results cannot be directly compared to prior evidence. However, and strengthening the role of parents (Axelin et al, 2015;Ferreira et al, 2021;Marfurt-Russenberger et al, 2016;McNair et al, 2020) support our findings regarding professionals' abilities and willing- pain relief method as non-nutritive sucking coupled with glucose (Koukou et al, 2022;Ullsten et al, 2021) is also known, and parents described professionals using it. In the future, it would be important for health professionals to recognise these situations, where parents can be involved in both the assessment of pain and its treatment with non-pharmacological methods.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Parents' experiences with IPC in the context of neonatal pain management has not previously been studied, so our results cannot be directly compared to prior evidence. However, and strengthening the role of parents (Axelin et al, 2015;Ferreira et al, 2021;Marfurt-Russenberger et al, 2016;McNair et al, 2020) support our findings regarding professionals' abilities and willing- pain relief method as non-nutritive sucking coupled with glucose (Koukou et al, 2022;Ullsten et al, 2021) is also known, and parents described professionals using it. In the future, it would be important for health professionals to recognise these situations, where parents can be involved in both the assessment of pain and its treatment with non-pharmacological methods.…”
Section: Discussionsupporting
confidence: 80%
“…Most wards have agreed to use certain pain assessment measures. The most common evidence‐based non‐pharmacological pain relief method as non‐nutritive sucking coupled with glucose (Koukou et al, 2022; Ullsten et al, 2021) is also known, and parents described professionals using it. In the future, it would be important for health professionals to recognise these situations, where parents can be involved in both the assessment of pain and its treatment with non‐pharmacological methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its advantages are that it avoids mechanical ventilation, potentially neurotoxic drugs and prolonged postinterventional monitoring. In principle, procedural stress and minor pain in neonate and preterm infants can be effectively reduced by nonpharmacological measures such as breastfeeding, nonnutritive sucking or facilitated tucking [56,57 ▪▪ ]. In older children, cognitive methods and hypnosis can be used instead of or in addition to procedural sedation.…”
Section: Adjuncts To Pharmacological Sedationmentioning
confidence: 99%
“…Pain is a common yet serious adverse stimulus faced by neonates in the neonatal intensive care unit (NICU). [ 1 ] A previous study [ 2 ] has shown that NICU neonates have experienced an average of 7.5 to 17.3 times of operational pain every day in the first 2 weeks after hospitalization. A Chinese survey [ 3 ] has shown that the median number of pain causing operations received by children every day was 20.…”
Section: Introductionmentioning
confidence: 99%